Hambatan Penerapan Table Official pada Indonesian Basketball League (IBL) (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the obstacles of table official in the implementation of the Indonesian Basketball League Series I Semarang. The research used qualitative method through observation, interviews, and documentation. The subjects of this study were table official and several steering committees on duty at IBL. The data analysis technique used was data triangulation technique. Data analysis with data collection, reduction, and conclusion. The result of the research conducted showed that 1) the availability of equipment is good and has backup;2) there are obstacle for the shotclock operator to adjust in the match;3) several tools such as timers and buzzer do not have FIBA standard;4) the condition of the equipment is quite good;5) the function of the tool runs well;6) the tool can work in accordance with the procedure for using tools in FIBA regulation expect on the scoreboard;7) the desk clerk has not been given legality or a license to work;8) the condition before, during, and after match are in accordance with FIBA regulations;9) environmental conditions sush as spectators and weather can cause obstacles during the match. The results of the sudy indicate that there are several things that can hinder the application of table official equipment, table official and environmental conditions.